PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN - Marissa Grace Haque (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2020)
This study aims to determine the effect of product quality and price on purchasing decisions at PT. Berlian Multitama in Jakarta. The method used is explanatory research with analytical techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study the quality of products significantly influence the purchase decision of 46.5%, the hypothesis test obtained t count t table or (6.978 2.003). Price significantly influences the purchase decision of 36.0%, the hypothesis test is obtained t arithmetic t table or (5.613 2.003). Product quality and price simultaneously have a significant effect on purchasing decisions with a regression equation Y = 10.354 + 0.425X1 + 0.331X2 and the contribution effect is 55.9%, the hypothesis test is obtained F count F table or (34.821 2.770).